Association of Hyperuricemia With Proteinuria in Patients With Type 2 Diabetes Mellitus: Experience of a Tertiary Care Hospital - Shah, Mahnoor; Kamran, Muhammad Ali; Jehangir, Umer; Bansari, Shard Kumar; Saeed, Alina (Biological and Clinical Sciences Research Journal, 2025)
Diabetic nephropathy is a leading cause of chronic kidney disease and end-stage renal failure in patients with type 2 diabetes mellitus (T2DM). Albuminuria is an early marker of renal damage, while hyperuricemia has been increasingly recognized as a possible risk factor for kidney disease progression. Objective: To evaluate the relationship between elevated serum uric acid levels and the presence and severity of albuminuria in patients with type 2 diabetes. Methods: A retrospective, hospital-based study was conducted at Ziauddin University Hospital, Clifton Campus during June 2024 till November 2024. A total of 400 patients with T2DM were included using non-probability purposive sampling. Inclusion criteria were age >18 years, confirmed T2DM, serum uric acid ≥7 mg/dL, and spot urine albumin–creatinine ratio (UACR) >30 mg/g. Patients with UTI, stage 5 CKD, autoimmune disease, malignancy, or on medications affecting uric acid levels were excluded. Results: The mean serum uric acid level was 7.8 ± 0.6 mg/dL, and the mean UACR was 154.6 ± 85.2 mg/g. Macroalbuminuria was present in 30.5% of patients. The frequency of macroalbuminuria increased significantly with higher uric acid levels (p < 0.001). A significant positive correlation was observed between serum uric acid and UACR (r = 0.42, p < 0.001). Stratified analysis showed higher rates of macroalbuminuria among patients with longer diabetes duration and poorer glycemic control. Conclusion: It is concluded that hyperuricemia is significantly associated with increased albuminuria in patients with type 2 diabetes. Monitoring and managing serum uric acid levels may serve as a valuable approach in the early identification and prevention of diabetic nephropathy.